2010
DOI: 10.1177/039139881003301003
|View full text |Cite
|
Sign up to set email alerts
|

Early Gut Barrier Dysfunction in Patients with Severe Acute Pancreatitis: Attenuated by Continuous Blood Purification Treatment

Abstract: CBP can not only improve the general conditions but also effectively improve gut barrier dysfunction. The beneficial effect of CBP on gut barrier dysfunction is associated with the improvement of cytoskeletal instability, by downregulating iNOS through the removal of excess proinflammatory factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
2
38
0
Order By: Relevance
“…A former study has proved that CBP could ameliorate the prognosis of patients suffering from MOF via unknown mechanisms, which was in accordance with our results [16]. CBP can not only improve the general conditions but also effectively improve gut barrier dysfunction, whose beneficial effect on gut barrier dysfunction is associated with the improvement of cytoskeletal instability, by down-regulating iNOS through the removal of excess proinflammatory factors [25]. Another data showed that after CBP treatment, endothelial hyperpermeability induced by serum from severe acute pancreatitis (SAP) patients with lung injury was ameliorated [26].…”
Section: Discussionsupporting
confidence: 91%
“…A former study has proved that CBP could ameliorate the prognosis of patients suffering from MOF via unknown mechanisms, which was in accordance with our results [16]. CBP can not only improve the general conditions but also effectively improve gut barrier dysfunction, whose beneficial effect on gut barrier dysfunction is associated with the improvement of cytoskeletal instability, by down-regulating iNOS through the removal of excess proinflammatory factors [25]. Another data showed that after CBP treatment, endothelial hyperpermeability induced by serum from severe acute pancreatitis (SAP) patients with lung injury was ameliorated [26].…”
Section: Discussionsupporting
confidence: 91%
“…Although the complete sets of mRNAs and processes controlled by H19 in the intestinal epithelium remain to be fully elucidated, the fact that the prevention of miR-675 processing from H19 by HuR protected the epithelial barrier function highlights the impact of an individual lncRNA in controlling gut permeability in specific clinical settings. These findings are particularly significant in patients with traumatic damage, thermal injury, or shock and in patients recovering from major surgical operations, as acute gut barrier dysfunction occurs commonly in these clinical situations (12,64). In summary, our results indicate that the H19/ miR-675 axis downregulates the intestinal barrier function by inhibiting ZO-1 and E-cadherin expression posttranscriptionally, whereas HuR prevents miR-675 processing from H19 and is crucial for maintaining a normal barrier function under biological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, since inflammatory mediators play a role in pathogenesis of both septic and non-septic systemic inflammatory response syndromes, HCO-CVVHDF may be useful in either sterile or infected SAP. Moreover, there is evidence that cytokine removal can improve gut barrier function in patients with SAP [15], which could potentially prevent bacterial translocation, bacteremia and infection of necrotic tissues. There is also evidence that HCO-CVVHDF may restore native immunity competence and T-lymphocyte function, thus improving antibacterial immunity and contributing to prevent infective complications and late mortality [12].…”
Section: Discussionmentioning
confidence: 99%